Chemistry lecturers’ attitudes toward educational technology: Afghanistan lecturer perspective - Chuzairy Hanri; Sayed Abdul Aziz Ahmady Falah; Muhammad Abd Hadi Bunyamin; Sharifah Osman (Institute of Advanced Engineering and Science, 2022)
Teachers play important role in applying technology in teaching and learning especially their attitude towards educational technology. Therefore, this study aimed to determine Afghanistan’s chemistry lecturers’ attitudes and find out differences in technology attitudes based on gender. The random sampling was used to select 154 participants. The result shows the positive attitudes of Afghanistan chemistry lecturers toward using education technology in the class. Furthermore, based on the finding, there was no significant difference between male and female lecturers’ toward using educational technology in the class. The result of this study can be use by the Afghanistan’s Ministry of higher education (HEM) and all university managers to introduce modern education technology into the education system since Afghanistan lecturers seem ready to use it in class.